Engineering of an Osteoinductive and Growth Factor‐Free Injectable Bone‐Like Microgel for Bone Regeneration. Issue 11 (7th March 2023) - Subbiah, Ramesh; Lin, Edith Y.; Athirasala, Avathamsa; Romanowicz, Genevieve E.; Lin, Angela S. P.; Califano, Joseph V.; Guldberg, Robert E.; Bertassoni, Luiz E.
Abstract: Bone autografts remain the gold standard for bone grafting surgeries despite having increased donor site morbidity and limited availability. Bone morphogenetic protein‐loaded grafts represent another successful commercial alternative. However, the therapeutic use of recombinant growth factors has been associated with significant adverse clinical outcomes. This highlights the need to develop biomaterials that closely approximate the structure and composition of bone autografts, which are inherently osteoinductive and biologically active with embedded living cells, without the need for added supplements. Here, injectable growth factor‐free bone‐like tissue constructs are developed, that closely approximate the cellular, structural, and chemical composition of bone autografts. It is demonstrated that these micro‐constructs are inherently osteogenic, and demonstrate the ability to stimulate mineralized tissue formation and regenerate bone in critical‐sized defects in‐vivo. Furthermore, the mechanisms that allow human mesenchymal stem cells (hMSCs) to be highly osteogenic in these constructs, despite the lack of osteoinductive supplements, are assessed, whereby Yes activated protein (YAP) nuclear localization and adenosine signaling appear to regulate osteogenic cell differentiation. The findings represent a step toward a new class of minimally invasive, injectable, and inherently osteoinductive scaffolds, which are regenerative by virtue of their ability to mimic the tissue cellular and extracellular microenvironment, thus showing promise for clinical applications in regenerative engineering. Abstract : Here, the regenerative properties of a new class of cell‐laden nano‐scale mineralized collagen constructs that differentiates encapsulated cells via matrix stiffness and adenosine signaling, without growth factor supplementation are assessed. The regenerative capacity of this engineered bone graft in a calvarial defect model resembles reported tissue remodeling patterns for autologous bone regeneration and rivals the regenerative capacity of customary bone morphogenetic protein‐2 (BMP‐2) loaded collagen grafts.